ANALISIS POTENSI MEDIA PEMBELAJARAN CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD - Siti Aminah; Sita Isna Malyuna; Sumadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The integration of digital learning media has created new opportunities to improve science and social science (IPAS) instruction in elementary schools, particularly where students' learning outcomes remain unsatisfactory. Among the available platforms, Canva has attracted increasing attention for its ability to present instructional content through visually engaging and interactive designs. This study investigates its educational contribution by synthesizing evidence from previous research using a descriptive qualitative approach based on a literature review. Seven scholarly articles were retrieved from Google Scholar using the keywords